Development and evaluation of sustained release losartan potassium matrix tablet using kollidon SR as release retardant - Shahid Sarwar; Mohammad Salim Hossain (Universidade de São Paulo, 2012)
The present study was undertaken to develop sustained release (SR) matrix tablets of losartan potassium, an angiotensin-II antagonist for the treatment of hypertension. The tablets were prepared by direct compression method, along with Kollidon SR as release retardant polymer. The amount of losartan potassium remains fixed (100 mg) for all the three formulations whereas the amounts of Kollidon SR were 250 mg, 225 mg, and 200 mg for F-1, F-2, and F-3 respectively. The evaluation involves three stages: the micromeritic properties evaluation of granules, physical property studies of tablets, and in-vitro release kinetics studies. The USP apparatus type II was selected to perform the dissolution test, and the dissolution medium was 900 mL phosphate buffer pH 6.8. The test was carried out at 75 rpm, and the temperature was maintained at 37 ºC ± 0.5 ºC. The release kinetics was analyzed using several kinetics models. Higher polymeric content in the matrix decreased the release rate of drug. At lower polymeric level, the rate and extent of drug release were enhanced. All the formulations followed Higuchi release kinetics where the Regression co-efficient (R²) values are 0.958, 0.944, and 0.920 for F-1, F-2, and F-3 respectively, and they exhibited diffusion dominated drug release. Statistically significant (P<0.05) differences were found among the drug release profile from different level of polymeric matrices. The release mechanism changed from non-fickian (n=0.489 for F-1) to fickian (n=0.439 and 0.429 for F-2, and F-3 respectively) as a function of decreasing the polymer concentration. The Mean Dissolution Time (MDT) values were increased with the increase in polymer concentration. O presente estudo foi realizado para desenvolver (SR) matriz de comprimidos de liberação sustentada de losartana, um antagonista da angiotensina II, para o tratamento da hipertensão arterial. Os comprimidos foram preparados pelo método de compressão direta com Kollidon SR como polímero de liberação lenta. A quantidade de losartana potássica permanece fixa (100 mg) para todas as três formulações enquanto que as quantidades de Kollidon SR foram de 250 mg, 225 mg e 200 mg para F-1, F-2 e F-3, respectivamente. A avaliação envolve três etapas- propriedades micromeríticas dos grânulos, estudo das propriedades físicas dos comprimidos e estudos de cinética de liberação in vitro.. Selecionoou-se o aparelho USP tipo II para realizar o teste de dissolução em meio com 900 mL de tampão fosfato pH 6,8 . O teste foi realizado em 75 rpm e a temperatura foi mantida a 37 ºC ± 0.5 ºC. Analisou-se a cinética de liberação utilizando-se vários modelos cinéticos. Conteúdo mais alto de polímero na matriz reduziu a taxa de liberação do fármaco. Em níveis mais baixos de polímero, a taxa e a extensão de liberação do fármaco foram aumentados. Todas as formulações seguiram a cinética de liberação de Higuchi, em que os valores do coeficiente de regressão (R2) foram 0,958 , 0,944 e 0,920 para F-1, F-2 e F-3, respectivamente, e elas apresentaram liberação do fármaco dominada pela difusão. Encontraram-se diferenças estatisticamente significativas (P<0,05) entre os perfis de liberação do fármaco com diferentes níveis de matrizes poliméricas. O mecanismo de liberação mudou de não-fickiano(n=0,489 para F-1) para fickiano(n=0,439 e 0,429 para F-2 e F-3, respectivamente) em função da diminuição da concentração de polímero. Os valores do Tempo de Dissolução Média (TDM) aumentaram com o aumento da concentração polímero.